The Book of popular science : Vol. 8 (New York : Grolier, 1973)
Discusses the major sciences and their application in today's world.
Includes index.
Bibliography: v. 10, p. 267-290.
Keywords: Science; Technology; Natural history; Science; Technology; Natural history